EXTRACTION AND CHARACTERIZATION OF BLACK BETEL LEAF (PIPER ACRE BLUME.) ESSENTIAL OILS FROM EAST KALIMANTAN - MAULIDYA, VINA; HASANAH, ALIYA NUR; RIJAI, LAODE; MUCHTARIDI, MUCHTARIDI (International Journal of Applied Pharmaceutics, 2022)
Objective: To determine the extraction technique and content of linalool, as the dominant compound, in black betel essential oil from East Kalimantan using a validated analytical method. Methods: Extraction was carried out using steam distillation. Essential oils were assessed by observing the colour and solubility in ethanol. Using an Agilent GC-MS with a 5977B (GCMSD) detector, a DB-5MS column, and a helium gas carrier of 1 ml/minute. The level of dominant compounds was determined using a validated analytical method. Results: The essential oil had characteristics that met SNI standards. Based on the results of GC-MS, the dominant compound in five samples was linalool. Validation of the analytical method was carried out with the following conditions established: injector temperature 250 °C, oven temperature 40 °C with a 2 min holding time, reaching 125 °C with a 10 min holding time, reaching 250 °C with a 2 min holding time, reaching 340 °C with a 10 min holding time. The resulted in a linearity of 0.999; a 1.637% relative standard deviation for precision; 102.27% recovery value for accuracy; 0.4% LOD; and 1.2% LOQ. The percentage linalool content of the samples was found in the sample code MADSH 4 (10.56% with a standard deviation of 0.6169). Conclusion: The steam distillation extraction method can be used to obtain essential oil with characteristics that meet SNI standards. Based on the results of GC-MS, linalool is the dominant compound, with a concentration of 10.56% found in the MADSH4 sample.